Prepreg

The use of a prepreg configuration with reinforced fibers, high rubber state elastic modulus thermosetting resin, and thermoplastic resin layer addresses the challenges of joining fiber-reinforced composite materials by enabling efficient welding with enhanced bonding strength and reduced manufacturing time.

JP7647099B2Active Publication Date: 2025-03-18TORAY INDUSTRIES INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020542929
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-23
Filing Date
2020-05-15
Publication Date
2025-03-18
Estimated Expiration
2040-05-15

AI Technical Summary

Technical Problem

Existing methods for joining fiber-reinforced composite materials, such as those made from thermosetting resins and reinforced fibers, face challenges including lengthy bonding processes, insufficient bonding strength, especially at high temperatures, and increased manufacturing costs due to mechanical processing like drilling.

Method used

A prepreg configuration comprising reinforced fibers, a thermosetting resin with a high rubber state elastic modulus, and a thermoplastic resin layer that allows for welding of the composite materials, resulting in enhanced bonding strength and reduced manufacturing time.

Benefits of technology

The proposed solution enables efficient welding of fiber-reinforced composite materials with improved bonding strength, particularly at high temperatures, and increased compressive strength, thus reducing manufacturing time and costs while maintaining structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647099000005
    Figure 0007647099000005
  • Figure 0007647099000006
    Figure 0007647099000006
  • Figure 0007647099000001
    Figure 0007647099000001
Patent Text Reader

Abstract

The purpose of the present invention is provide: a prepreg which has excellent compression strength and an excellent interlayer fracture toughness value, which can be firmly integrated with other structural members when being melted and adhered thereto, and which is for manufacturing a laminate that is suitable as a structural material; and said laminate. This prepreg contains [A] reinforced fibers, [B] a thermosetting resin, and [C] a thermoplastic resin as components, wherein [B] has a rubber-state elastic modulus of 10 MPa or more at a temperature obtained by adding 50°C to the glass transition temperature in a state where the degree of curing is 90% or more, [C] is present in the surface of the prepreg, and [A] the reinforced fibers included in both a resin region containing [B] and a resin region containing [C] are present across the boundary surface between the two resin regions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a prepreg containing reinforcing fibers, a thermosetting resin, and a thermoplastic resin, and a laminate and a molded article containing reinforcing fibers, a thermoplastic resin, and a cured product of a thermosetting resin. [Background technology]

[0002] Fiber-reinforced composite materials, which are made by combining a thermosetting resin or a thermoplastic resin as a matrix with reinforcing fibers such as carbon fiber or glass fiber, have excellent mechanical properties such as strength and rigidity, heat resistance, and corrosion resistance while being lightweight, and have been applied to many fields such as aerospace, automobiles, railway vehicles, ships, civil engineering and construction, and sporting goods. However, these fiber-reinforced composite materials are not suitable for manufacturing parts or structures with complex shapes in a single molding process, and in the above applications, it is necessary to prepare a member made of the fiber-reinforced composite material and then integrate it with the same or different members. Mechanical joining methods such as bolts, rivets, and screws, and joining methods using adhesives are used as methods for integrating the same or different members with fiber-reinforced composite materials made of reinforcing fibers and thermosetting resins. Mechanical joining methods require a process of pre-processing the joint parts, such as drilling holes, which leads to a long manufacturing process and increased manufacturing costs, and there is also the problem that the material strength is reduced due to the drilling of holes. Bonding methods that use adhesives require a bonding process that includes preparing the adhesive and applying the adhesive, as well as a curing process, which lengthens the manufacturing process time. This has led to problems with the adhesive strength and reliability not being fully satisfactory.

[0003] Fiber-reinforced composite materials using a thermoplastic resin as a matrix can be used to join components by welding, in addition to the above-mentioned mechanical joining methods and joining using adhesives, so there is a possibility that the time required for joining components can be shortened. However, when mechanical properties at high temperatures and excellent resistance to chemicals are required, such as in aircraft structural components, there is an issue that the heat resistance and chemical resistance are insufficient compared to fiber-reinforced composite materials made of thermosetting resins and reinforcing fibers.

[0004] Here, Patent Document 1 discloses a method for bonding a fiber-reinforced composite material made of a thermosetting resin and reinforcing fibers via an adhesive.

[0005] Patent Document 2 shows a method for integrating a member made of a thermoplastic resin with a member made of a fiber-reinforced composite material made of a thermosetting resin. That is, a thermoplastic resin film is laminated on the surface of a prepreg sheet made of reinforcing fibers and a thermosetting resin, and a fiber-reinforced composite material is obtained by heating and pressing. The obtained fiber-reinforced composite material is then placed in a mold, and the thermoplastic resin is injection-molded to bond the thermoplastic resin member formed by injection molding to the fiber-reinforced composite material.

[0006] Furthermore, Patent Document 3 discloses a method for producing a laminate in which a thermoplastic resin adhesive layer is formed on the surface of a composite material made of a thermosetting resin and reinforcing fibers, and describes that the laminate exhibits an adhesive effect with other components via the thermoplastic resin. Patent Document 4 discloses a prepreg in which particles, fibers, or a film made of a thermoplastic resin are disposed on the surface layer of a prepreg made of reinforcing fibers and a thermosetting resin, and also discloses a fiber-reinforced composite material thereof. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2018-161801 A [Patent Document 2] Japanese Patent Application Publication No. 10-138354 [Patent Document 3] Patent No. 3906319 [Patent Document 4] Japanese Patent Application Publication No. 8-259713 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the technique disclosed in Patent Document 1 is a method of bonding fiber-reinforced composite materials made of reinforcing fibers and thermosetting resins with an adhesive, and since the thermosetting resin is a matrix resin, welding cannot be applied as a method of bonding between fiber-reinforced composite materials as it is. Since it takes time for the adhesive to harden, there is a problem that the bonding process takes time, and furthermore, the bond strength achieved is insufficient.

[0009] In the method described in Patent Document 2, the bonding strength at the bonded portion between the thermosetting resin and the thermoplastic resin film in the fiber reinforced composite material was insufficient.

[0010] The fiber-reinforced composite material according to Patent Document 3 can be integrated by welding via a thermoplastic resin, and exhibits excellent bonding strength at room temperature, but the bonding strength at high temperatures is insufficient.

[0011] Patent Document 4 shows that the interlaminar fracture toughness value can be improved by using particles, fibers, or films made of a thermoplastic resin, but this method does not provide sufficient bonding strength at the boundary between the thermosetting resin and the thermoplastic resin in the fiber-reinforced composite material.

[0012] Therefore, an object of the present invention is to provide a prepreg, a laminate, and an integrally molded product which can be joined by welding to the same or different members, exhibits excellent bonding strength, particularly under high temperature environments, and further has excellent compressive strength and interlaminar fracture toughness values, thereby providing a laminate suitable as a structural material. [Means for solving the problem]

[0013] In order to solve such problems, the prepreg of the present invention has the following configuration.

[0014] That is, a prepreg containing the following components [A], [B], and [C], in which [B] has a rubber-state elastic modulus of 10 MPa or more at a temperature obtained by adding 50°C to the glass transition temperature when the degree of cure is 90% or more, [C] is present on the surface of the prepreg, and the reinforcing fibers of [A] contained in both resin regions are present across the boundary between the resin region containing [B] and the resin region containing [C]. [A] Reinforced fiber [B] Thermosetting resin [C] Thermoplastic resin.

[0015] Furthermore, the laminate of the present invention has the following configuration.

[0016] That is, the laminate comprises layers containing the following components [A], [C] and [D], in which [D] has a rubber-state elastic modulus of 10 MPa or more at a temperature 50°C above the glass transition temperature, and in which the reinforcing fibers of [A] contained in both resin regions are present across the boundary between a resin region containing [C] and a resin region containing [D]. [A] Reinforced fiber [C]Thermoplastic resin [D] Cured thermosetting resin. Effect of the Invention

[0017] The prepreg of the present invention uses a thermosetting resin and a thermoplastic resin, and the two are firmly bonded together. In addition, good welding with the same or different members is possible. Therefore, compared to conventional fiber-reinforced composite materials consisting of a thermosetting resin and reinforcing fibers, the time required for the bonding process can be shortened, and the molding of structural members can be accelerated. Furthermore, by having excellent rubber-state elastic modulus at a predetermined temperature, excellent compressive strength and bonding strength in a high-temperature environment are exhibited, and a laminate excellent as a structural material can be obtained. The laminate of the present invention shows excellent performance as a structure by being applied to aircraft structural members, windmill blades, automobile structural members, and computer applications such as IC trays and notebook computer housings, and the like. In addition, by using the prepreg of the present invention, it is possible to greatly reduce the molding time and molding cost of products related to the above applications. [Brief description of the drawings]

[0018] [Figure 1] 3 is a schematic diagram of a prepreg or laminate according to the present invention, showing a cross section perpendicular to the plane of the prepreg or laminate according to FIG. 2. [Diagram 2] FIG. 1 is a schematic diagram of a cross section perpendicular to a prepreg plane or a laminate plane in the present invention, which helps to explain the method of measuring the roughness average length RSm and the roughness average height Rc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The reinforcing fibers of the component [A] used in the present invention include glass fibers, carbon fibers, metal fibers, aromatic polyamide fibers, polyaramid fibers, alumina fibers, silicon carbide fibers, boron fibers, and basalt fibers. These may be used alone or in combination of two or more types. These reinforcing fibers may be surface-treated. Examples of surface treatments include metal deposition treatment, treatment with a coupling agent, treatment with a sizing agent, and additive attachment treatment. These reinforcing fibers also include conductive reinforcing fibers. Carbon fibers are preferably used as reinforcing fibers because of their low specific gravity, high strength, and high elastic modulus.

[0020] Commercially available carbon fibers include "TORAYCA (registered trademark)" T800G-24K, "TORAYCA (registered trademark)" T800S-24K, "TORAYCA (registered trademark)" T700G-24K, "TORAYCA (registered trademark)" T700S-24K, "TORAYCA (registered trademark)" T300-3K, and "TORAYCA (registered trademark)" T1100G-24K (all manufactured by Toray Industries, Inc.).

[0021] The form and arrangement of the reinforcing fibers can be appropriately selected from those in which the reinforcing fibers are arranged in one direction, a laminate of reinforcing fibers arranged in one direction, or a woven fabric, etc., but in order to obtain a laminate that is lightweight and has a higher level of durability, it is preferable that the reinforcing fibers in each prepreg be in the form of continuous fibers such as long fibers (fiber bundles) arranged in one direction or a woven fabric.

[0022] The reinforcing fiber bundle may be composed of a plurality of fibers of the same form, or may be composed of a plurality of fibers of different forms. The number of reinforcing fibers constituting one reinforcing fiber bundle is usually 300 to 60,000, but considering the production of the base material, it is preferably 300 to 48,000, more preferably 1,000 to 24,000. It may be within a range that is a combination of any of the above upper limits and any of the above lower limits.

[0023] For the reinforcing fiber of the component [A], it is preferable that the strand tensile strength measured according to the resin-impregnated strand test method of JIS R7608 (2007) is 5.5 GPa or more, since a laminate having excellent bonding strength in addition to tensile strength can be obtained. It is even more preferable that the strand tensile strength is 5.8 GPa. The bonding strength referred to here refers to the tensile shear bonding strength obtained according to ISO4587:1995 (JIS K6850 (1994)).

[0024] The component [B] used in the present invention is a thermosetting resin having a rubber-state elastic modulus of 10 MPa or more at a temperature obtained by adding 50° C. to the glass transition temperature at a degree of cure of 90% or more. The component [B] can be made to have a degree of cure of 90% or more by heating and curing the thermosetting resin of the component [B] and the thermosetting resin composition before curing, which is specified as the curing agent, under specified conditions. Heat curing under specified conditions refers to first heating at 135° C. for 2 hours or 180° C. for 2 hours, and then further heating as necessary until the degree of cure reaches 90% or more. The degree of cure of the thermosetting resin cured product obtained by heating at 135° C. for 2 hours or 180° C. for 2 hours is measured, and if the degree of cure is 90% or more, the thermosetting resin cured product can be used for characteristic evaluation. If the degree of cure is less than 90% at the heating temperature and time of 135° C. for 2 hours or 180° C. for 2 hours, the degree of cure is confirmed by heating at 180° C. for 2 hours. If the degree of cure after post-heating is less than 90%, heat is increased in sequence to 200°C for 1 hour, 220°C for 1 hour, and 240°C for 1 hour until the degree of cure is 90% or more. If the degree of cure does not reach 90% even after heating at 240°C for 1 hour, heat at a temperature of 300°C or less until the degree of cure is 90% or more, and the desired thermosetting resin cured product can be obtained and used for characteristic evaluation.

[0025] Here, the degree of cure is a value calculated by calculating the heat generation amount of each of the thermosetting resin of the component [B], the thermosetting resin composition before curing specified as the curing agent, and the cured product of the thermosetting resin as the area of ​​each peak that appears as an exothermic reaction when performing differential scanning calorimetry at a temperature increase rate of 10 ° C. / min in an inert gas atmosphere, and then calculating the value by the following formula. In addition to the component [B] contained in the prepreg, a resin having the same structure as the thermosetting resin and the curing agent specified can also be prepared and used for measurement. Here, if the curing agent cannot be specified, 4,4'-diaminodiphenyl sulfone may be used as the curing agent in the above composition. In addition, compounds such as a curing catalyst and a viscosity modifier, which will be described later in the examples, can be preferably used as elements that can constitute the above composition, but these are not particularly limited as long as they do not affect the measurement results. Degree of curing (%)=((amount of heat generated by the composition containing a thermosetting resin before curing)−(amount of heat generated by the cured product of the thermosetting resin)) / (amount of heat generated by the composition containing a thermosetting resin before curing)×100.

[0026] In addition, the storage modulus at a temperature obtained by adding 50°C to the glass transition temperature obtained from the storage modulus curve of the dynamic viscoelasticity measurement (torsion measurement) of the thermosetting resin cured product is determined according to JIS K7244-7 (2007), and is defined as the rubber state modulus of the present invention. If the rubber state modulus of the present invention is less than 10 MPa, the compression strength of the laminate and the bonding strength at high temperatures when the laminate and a member are bonded and integrated cannot be sufficiently increased. The rubber state modulus is more preferably 12 MPa or more, and more preferably 15 MPa or more. There is no particular limit to the upper limit of the rubber state modulus, but the upper limit of a typical thermosetting resin cured product is 50 MPa.

[0027] The thermosetting resin cured product of the component [D] in the present invention can be obtained by heating and curing the thermosetting resin. Regarding the judgment of the curing of the component [D] contained in the laminate, when the laminate is subjected to differential scanning calorimetry under an inert gas atmosphere at a heating rate of 10°C / min, if the area of ​​the peak (residual heat) appearing as an exothermic reaction is 50 J / g or less, it can be judged to be a substantially cured product. Alternatively, when the thermosetting resin composition before curing can be specified, the degree of curing may be calculated by the above formula, and if it is 90% or more, it may be considered to be a cured product. When the prepreg of the present invention is used, the thermosetting resin corresponds to the component [B]. The laminate of the present invention does not necessarily have to be produced via a prepreg, and may be produced by a resin transfer molding method described later.

[0028] Examples of the thermosetting resin used in the component [B] include unsaturated polyester resin, vinyl ester resin, epoxy resin, phenol resin, urea resin, melamine resin, polyimide resin, cyanate ester resin, bismaleimide resin, benzoxazine resin, copolymers, modified products thereof, and resins obtained by blending at least two of these. To improve impact resistance, an elastomer or rubber component may be added to the thermosetting resin. Among these, epoxy resin is preferable because it has excellent mechanical properties, heat resistance, and adhesion to reinforcing fibers. Examples of the base resin of the epoxy resin include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD ​​type epoxy resin, and bisphenol S type epoxy resin; brominated epoxy resins such as tetrabromobisphenol A diglycidyl ether; epoxy resins having a biphenyl skeleton, epoxy resins having a naphthalene skeleton, epoxy resins having a dicyclopentadiene skeleton, novolac type epoxy resins such as phenol novolac type epoxy resin and cresol novolac type epoxy resin; Examples of the epoxy resins include glycidyl amine type epoxy resins such as phenol, N,N,O-triglycidyl-p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, N,N,N',N'-tetraglycidyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, N,N-diglycidylaniline, and N,N-diglycidyl-o-toluidine, resorcinol diglycidyl ether, and triglycidyl isocyanurate.

[0029] The thermosetting resin, which is the component [B] of the present invention, preferably contains an epoxy resin, and contains 40 to 100 parts by mass of a glycidylamine type epoxy resin containing three or more glycidyl groups per 100 parts by mass of the total epoxy resin contained in the thermosetting resin, since a cured product with a high rubber-state elastic modulus can be obtained, which is a more preferred embodiment. Examples of the glycidylamine type epoxy resin containing three or more glycidyl groups include N,N,O-triglycidyl-m-aminophenol, N,N,O-triglycidyl-p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, N,N,N',N'-tetraglycidyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, and N,N,N',N'-tetraglycidyl-m-xylylenediamine.

[0030] Examples of the curing agent for the epoxy resin include dicyandiamide, aromatic amine compounds, phenol novolac resins, cresol novolac resins, polyphenol compounds, imidazole derivatives, tetramethylguanidine, thiourea-added amines, carboxylic acid hydrazides, carboxylic acid amides, and polymercaptans.

[0031] In particular, by using an aromatic amine curing agent as a curing agent for an epoxy resin, an epoxy resin having good heat resistance can be obtained. Examples of the aromatic amine compound include 3,3'-diisopropyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-t-butyl-4,4'-diaminodiphenyl sulfone, 3,3'-diethyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3'-diisopropyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-t-butyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenyl sulfone, 3,3'-di Examples of the alkylaminodiphenyl sulfone include isopropyl-5,5'-diethyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-t-butyl-5,5'-diethyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetraisopropyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-t-butyl-5,5'-diisopropyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetra-t-butyl-4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, and 3,3'-diaminodiphenyl sulfone.

[0032] Furthermore, the thermosetting resin of the component [B] preferably contains a thermoplastic resin component soluble in the thermosetting resin in a dissolved state as a viscosity modifier. Such a thermoplastic resin component is a different thermoplastic resin component from the component [C]. Here, "soluble in the thermosetting resin" refers to the presence of a temperature range in which a homogeneous phase is formed by heating or heating and stirring a mixture of a thermoplastic resin component and a thermosetting resin. Here, "forming a homogeneous phase" refers to a state in which no separation is visible to the naked eye. Here, "dissolved state" refers to a state in which a thermosetting resin containing a thermoplastic resin component is in a certain temperature range and forms a homogeneous phase. Once a homogeneous phase is formed in a certain temperature range, separation may occur outside that temperature range, for example at room temperature.

[0033] The thermoplastic resin component soluble in the thermosetting resin of the component [B] is preferably a thermoplastic resin having a bond selected from the group consisting of carbon-carbon bonds, amide bonds, imide bonds, ester bonds, ether bonds, carbonate bonds, urethane bonds, thioether bonds, sulfone bonds and carbonyl bonds in the main chain. This thermoplastic resin component may have a partially crosslinked structure and may be crystalline or amorphous. In particular, at least one resin selected from the group consisting of polyamide, polycarbonate, polyacetal, polyphenylene oxide, polyphenylene sulfide, polyarylate, polyester, polyamideimide, polyimide, polyetherimide, polyimide having a phenyltrimethylindane structure, polysulfone, polyethersulfone, polyetherketone, polyetheretherketone, polyaramid, polyvinyl formal, polyvinyl butyral, phenoxy resin, polyethernitrile and polybenzimidazole is suitable. In order to obtain good heat resistance, from the viewpoint of being less likely to cause thermal deformation when used as a molded article, it is preferable for the material to have a glass transition temperature of 150°C or higher, more preferably 170°C or higher. Suitable examples of the material include polyetherimide and polyethersulfone.

[0034] In terms of improving flame retardancy, it is also one of the preferred embodiments to include a phosphorus compound in the composition containing the thermosetting resin of the component [B]. However, if the amount of phosphorus is large, the bending strength of the cured thermosetting resin may decrease. For this reason, it is preferable that the phosphorus atom concentration in the composition is 0.1 mass% or more and 1.0 mass% or less, since a cured thermosetting resin with excellent bending strength can be obtained.

[0035] Regardless of whether or not it contains a phosphorus compound, the component [B] contained in the prepreg of the present invention preferably has a bending strength of 150 MPa or more when the degree of cure is 90% or more. The component [D] contained in the laminate of the present invention has a bending strength of 150 MPa or more. When such a cured product is contained in the laminate of the present invention, it is preferable because the bonding strength when the laminate and a member are bonded is excellent. The bending strength can be determined by a three-point bending test based on JIS K7171 (1994). When determining the bending strength of the above-mentioned components contained in the prepreg or laminate, the type of thermosetting resin is specified, and the same type of uncured resin is made into a composition in the same manner as in the measurement of the degree of cure, and subjected to the measurement of bending strength. At this time, an uncured resin having the same structure as the thermosetting resin contained in the prepreg or laminate to be measured may be prepared and subjected to the measurement. In addition, there is no particular limit to the upper limit of the bending strength, but the upper limit of a typical thermosetting resin cured product is 500 MPa.

[0036] The thermoplastic resin constituting the component [C] is not particularly limited, and examples thereof include polyester resins (polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate, liquid crystal polyester, etc.), polyolefin resins (polyethylene, polypropylene, polybutylene, etc.), styrene resins, urethane resins, polyoxymethylene, polyamide resins (aliphatic polyamides such as polyamide 6 and polyamide 66, semi-aromatic polyamides, alicyclic polyamides, etc.), polycarbonate, polymethyl methacrylate, polyvinyl chloride, polyphenylene sulfide, polyphenylene ether, modified polyphenylene ether, polyimide, polyamideimide, polyetherimide, polysulfone, modified polysulfone, polyethersulfone, polyketone, polyarylene ether ketone (polyether ketone, polyether ether ketone, polyether ketone ketone, etc.), polyarylate, polyether nitrile, phenolic resins, and phenoxy resins. Furthermore, these thermoplastic resins may be copolymers or modified products of the above-mentioned resins, and / or resins in which two or more kinds are blended.

[0037] Among these, from the viewpoint of heat resistance, it is preferable that the thermoplastic resin of the component [C] contains 60% by weight or more of one or more types selected from crystalline thermoplastic resins having a glass transition temperature of 80° C. or higher and amorphous thermoplastic resins having a glass transition temperature of 160° C. or higher. It is particularly preferable that the thermoplastic resin of the component [C] contains 60% by weight or more of one or more types selected from polyarylene ether ketone, polyphenylene sulfide, and polyetherimide.

[0038] In order to improve impact resistance, an elastomer or rubber component may be added to the thermosetting resin or thermoplastic resin. Furthermore, depending on the application, etc., the thermosetting resin or thermoplastic resin may contain other fillers or additives as appropriate within the scope of the present invention. For example, inorganic fillers, flame retardants, conductive agents, crystal nucleating agents, ultraviolet absorbers, antioxidants, vibration dampers, antibacterial agents, insect repellents, deodorants, coloring inhibitors, heat stabilizers, release agents, antistatic agents, plasticizers, lubricants, colorants, pigments, dyes, foaming agents, foam control agents, coupling agents, etc. may be mentioned.

[0039] In the prepreg of the present invention, the reinforcing fibers [A] contained in both resin regions are present across the boundary surface between the resin region containing [B] and the resin region containing [C].

[0040] The presence of [A] included in both resin regions across the boundary surface of both resin regions can be confirmed by observing a cross section obtained by cutting perpendicularly to the plane direction. An example is shown in FIG. 2. In the observation image 9 in FIG. 2, in the case of a prepreg, the resin region 7 including the component [C] is in close contact with the resin region 8 including the component [B], and the surface where the resin region 7 including the component [C] and the resin region 8 including the component [B] are in close contact is illustrated as the boundary surface 10. In addition, multiple components [A] 6 exist on the boundary surface 10. The component [A] 6 on the boundary surface 10 is in contact with both the resin region 7 including the component [C] and the resin region 8 including the component [B]. In this way, the state in which the components [C] and [B] are in contact with the periphery of the reinforcing fiber can be said to be a state in which the reinforcing fiber is "included in both resin regions across the boundary surface."

[0041] Furthermore, when the prepreg of the present invention is viewed in plan, in a cross section perpendicular to the prepreg plane containing the fibers of [A] present across both resin regions, i.e., in a cross section obtained by cutting perpendicularly to the prepreg plane direction, from a direction at an angle of 45 degrees different from the fiber direction of any [A] contained in both resin regions, regardless of whether it is clockwise or counterclockwise, it is preferable that the roughness average length RSm of the cross-sectional curve formed by the boundary surface between both resins, as defined in JIS B0601 (2001), is 100 μm or less, and the roughness average height Rc is 3.5 μm or more.

[0042] It is also preferable that the resin region containing [B] and the resin region containing [C] are adjacent to each other in a layered state to form the boundary surface. Adjacent to each other in a layered state means that both continuous resin regions are adjacent to each other, as shown in Fig. 2, for example, and this can be confirmed by observing a cross section obtained by cutting the prepreg perpendicular to the planar direction.

[0043] The presence of the reinforcing fibers [A] contained in both resin regions across the boundary between the resin region containing the component [B] and the resin region containing the component [C] improves the strength of the resin region containing the component [C] and improves the bonding strength. The component [A] present on the boundary surface is chemically or / and physically bonded to the components [B] and [C], thereby improving the adhesion between the resin region containing the component [B] and the resin region containing the component [C]. The number of components [A] present on the boundary surface may be one or more, and the upper limit number is not particularly limited, but is 200 in the observation range described below.

[0044] The boundary surface between the resin region containing component [B] and the resin region containing component [C] is observed in a cross section perpendicular to the prepreg plane containing the fibers of [A] that exist across both resin regions, from a direction that differs by 45 degrees, regardless of whether it is clockwise or counterclockwise, with respect to any fiber direction of [A] contained in both resin regions, in a plan view of the prepreg, i.e., from a viewpoint perpendicular to the prepreg plane direction. By observing the state of the resin region at the boundary surface in such a cross section, the adhesion strength in the fiber direction and in the direction perpendicular to the fiber direction can be evaluated simultaneously.

[0045] In such cross-sectional observation, when the roughness average length RSm of the cross-sectional curve formed by the boundary surface, as defined by JIS B0601 (2001), is 100 μm or less, not only the chemical or / and physical bonding force but also the mechanical bonding force of entanglement is added, and the resin region containing the component [B] and the resin region containing the component [C] are less likely to peel off, which is preferable. The lower limit is not particularly limited, but is preferably 15 μm or more from the viewpoint of avoiding a decrease in the mechanical bonding force due to stress concentration. In addition, when the roughness average height Rc of the cross-sectional curve is 3.5 μm or more, not only the mechanical bonding force due to entanglement is expressed, but also the component [A] present on the boundary surface is chemically or / and physically bonded to the component [B] and the component [C], and the adhesive force between the resin region containing the component [B] and the resin region containing the component [C] is improved, which is preferable. A more preferred range of the average roughness height Rc of the cross-sectional curve is 10 μm or more, at which the component [A] is more likely to be included in both resin regions and the adhesive strength is further improved, and particularly preferably 20 μm or more. The upper limit is not particularly limited, but is preferably 100 μm or less from the viewpoint of avoiding a decrease in mechanical bonding strength due to stress concentration.

[0046] Here, the method for measuring the roughness average height Rc and the roughness average length RSm of the cross-sectional curve can be a known method. For example, after curing the component [B], the method for measuring from a cross-sectional image acquired using X-ray CT, the method for measuring from an elemental analysis mapping image by an energy dispersive X-ray spectrometer (EDS), or the method for measuring from a cross-sectional observation image by an optical microscope, a scanning electron microscope (SEM), or a transmission electron microscope (TEM) can be mentioned. In the observation, the component [B] and / or the component [C] may be dyed to adjust the contrast. In the image obtained by any of the above methods, the roughness average height Rc and the roughness average length RSm of the cross-sectional curve are measured in a range of 500 μm square.

[0047] An example of a method for measuring the roughness average height Rc and roughness average length RSm of a cross-sectional curve (cross-sectional curve element measuring method 1) is shown in FIG. 2. Using an end 11 on the resin region side including the component [B] of a rectangular observation image 9 as a reference line, vertical base lines 12 are drawn at 5 μm intervals from the resin region 8 including the component [B] toward the resin region 7 including the component [C]. The point where the vertical base line drawn from the reference line first intersects with the component [C] is plotted, and the line connecting the plotted points is defined as a cross-sectional curve 13. A filtering process based on JIS B0601 (2001) is performed on the obtained cross-sectional curve 13, and the roughness average height Rc and roughness average length RSm of the cross-sectional curve 13 are calculated.

[0048] From the viewpoint of realizing excellent mechanical properties, it is preferable that the resin region containing [B] and the resin region containing [C] are adjacent to each other in a layered structure to form the boundary surface.

[0049] In the prepreg of the present invention, the weight per unit area of ​​the thermoplastic resin of the component [C] is 10 g / m 2 It is preferable that the thickness is 10 g / m or more. 2 If the thickness is more than this, a sufficient thickness for achieving excellent bonding strength can be obtained, and more preferably, 20 g / m 2 The upper limit is not particularly limited, but is preferably 500 g / m because the amount of thermoplastic resin is not too large compared to the reinforcing fibers and a laminate excellent in specific strength and specific elastic modulus can be obtained. 2 Here, the basis weight is the weight per 1 m of prepreg. 2 This refers to the mass (g) of the component [C] contained per unit.

[0050] The prepreg of the present invention has a reinforcing fiber amount per unit area of ​​30 to 2,000 g / m 2 It is preferable that the amount of reinforcing fibers is 30 g / m 2 When the amount of reinforcing fibers is 2,000 g / m or more, the number of layers required to obtain a predetermined thickness during laminate molding can be reduced, and the work can be simplified. 2 When it is equal to or less than this, the drape property of the prepreg is likely to be improved.

[0051] The reinforcing fiber mass content of the prepreg of the present invention is preferably 30 to 90 mass%, more preferably 35 to 85 mass%, and even more preferably 40 to 80 mass%. It may be a range that is a combination of any of the above upper limits and any of the above lower limits. When the reinforcing fiber mass content is 30 mass% or more, the amount of resin is not too large compared to the fibers, and the advantages of a laminate having excellent specific strength and specific elastic modulus are easily obtained, and when molding the laminate, the amount of heat generated during curing is unlikely to be excessively high. In addition, when the reinforcing fiber mass content is 90 mass% or less, impregnation failure of the resin is unlikely to occur, and the voids in the obtained laminate are likely to be reduced.

[0052] The laminate of the present invention satisfies the following requirements: It contains layers containing components [A], [C] and [D], [D] has a rubber-state elastic modulus of 10 MPa or more at a temperature 50°C above its glass transition temperature, and the reinforcing fibers of [A] contained in both resin regions are present across the boundary between a resin region containing [C] and a resin region containing [D].

[0053] The presence of [A] contained in both resin regions across the boundary surface between the two resin regions can be confirmed by observing a cross section obtained by cutting the laminate perpendicular to the planar direction, in the same manner as the confirmation method for the prepreg described above.

[0054] An example is shown in FIG. 2. In the observation image 9 in FIG. 2, in the case of a laminate, the resin region 7 containing the component [C] is in close contact with the resin region 8 containing the component [D], and the surface where the resin region 7 containing the component [C] and the resin region 8 containing the component [D] are in close contact is illustrated as an interface 10. In addition, a plurality of components [A] 6 are present on the interface 10. The component [A] 6 on the interface 10 is in contact with both the resin region 7 containing the component [C] and the resin region 8 containing the component [D]. In this manner, a state in which the components [C] and [D] are in contact with the periphery of the reinforcing fiber can be said to be a state in which the reinforcing fiber is "included in both resin regions across the interface."

[0055] Furthermore, when the laminate of the present invention is viewed in plan, the cross section perpendicular to the plane of the laminate containing [A] existing across both resin regions, i.e., the observed cross section obtained by cutting perpendicularly to the plane direction of the laminate, at an angle of 45 degrees from a viewpoint perpendicular to the plane direction of the laminate, regardless of whether the fiber direction of any [A] contained in both resin regions is clockwise or counterclockwise, is preferably such that the roughness average length RSm defined by JIS B0601 (2001) of the cross section curve formed by the boundary surface where both resin regions are in close contact is 100 μm or less and the roughness average height Rc is 3.5 μm or more. It is more preferable that the roughness average height Rc is 10 μm or more. The lower limit value of RSm and the upper limit value of Rc are not particularly limited, but from the viewpoint of concern about a decrease in mechanical bonding force due to stress concentration, RSm is preferably 15 μm or more and Rc is preferably 100 μm or less.

[0056] The method for measuring the roughness average height Rc and roughness average length RSm of the cross-sectional curve can be determined by the above-mentioned method, similarly to the measuring method for the prepreg of the present invention.

[0057] From the viewpoint of realizing excellent mechanical properties, it is preferable that the resin region containing [C] and the resin region containing [D] are adjacent to each other in a layered state to form the boundary surface. The adjacent layered state refers to a state in which both continuous resin regions are adjacent to each other, as shown in Fig. 2, for example, and can be confirmed by observing a cross section obtained by cutting the laminate perpendicular to the planar direction.

[0058] The laminate of the present invention can be produced by a molding method such as press molding, autoclave molding, bagging molding, wrapping tape method, internal pressure molding, hand lay-up method, filament winding method, pultrusion method, resin injection molding method, and resin transfer molding method.

[0059] The laminate of the present invention can be produced by laminating the above-mentioned prepreg of the present invention alone or with other prepregs to form at least a part of a layer, and curing the laminate by applying pressure and heat. The method for applying heat and pressure includes, for example, press molding, autoclave molding, bagging molding, wrapping tape method, internal pressure molding, etc.

[0060] In the laminate of the present invention, the thermoplastic resin of the component [C] is present on the surface or between the layers. It is preferable that the component [C] is present both on the surface and between the layers. The presence of the thermoplastic resin of the component [C] on the surface of the laminate allows the laminate of the present invention to be joined to the same or different members by welding through the component [C], while the presence of the thermoplastic resin of the component [C] between the layers of the laminate provides excellent interlaminar fracture toughness (G IC and G IIC ) is obtained.

[0061] The laminate of the present invention can be integrated (welded) with the laminate through the component [C] by bonding another member, i.e., a member (adherend) of the same type and / or different type as the member constituting the laminate, to the component [C] present on the surface of the laminate by some heating means. Examples of different members (adherends) include members made of thermoplastic resins and members made of metal materials. The member made of thermoplastic resin may contain reinforcing fibers, fillers, etc. The integration method is not particularly limited, and examples thereof include heat welding, vibration welding, ultrasonic welding, laser welding, resistance welding, induction welding, insert injection molding, and outsert injection molding.

[0062] The strength of the joint of the integrated members can be evaluated based on ISO4587:1995 (JIS K6850 (1994)). The tensile shear bond strength measured based on ISO4587:1995 is preferably 25 MPa or more when the test environment temperature is 23 ° C, more preferably 28 MPa or more. In general, if it is 20 MPa or more, the laminate can be used for bonding structural materials, and is a higher strength than the tensile shear bond strength (about 10 MPa) of a general adhesive when the test environment temperature is 23 ° C. In applications requiring mechanical properties in high temperature environments, it is preferable that the bond strength is 13 MPa or more when evaluated based on ISO4587:1995 when the test environment temperature is 80 ° C, more preferably 16 MPa or more. The higher the tensile shear bond strength, the more preferable it is, and there is no particular upper limit, but for a typical integrated laminate, the tensile shear bond strength at a test environment temperature of 23 ° C or 80 ° C is an upper limit of 200 MPa.

[0063] The laminate of the present invention is preferably used in aircraft structural members, wind turbine blades, automobile exterior panels, computer applications such as IC trays and notebook computer housings, and sports applications such as golf shafts and tennis rackets. EXAMPLES

[0064] The present invention will be described in detail below with reference to examples. However, the scope of the present invention is not limited to these examples. The unit "parts" in the composition ratio means parts by mass unless otherwise noted. Furthermore, the measurements of various properties were performed under an environment of a temperature of 23°C and a relative humidity of 50% unless otherwise noted.

[0065] <Materials used in the Examples and Comparative Examples> The following components [A], [B], [C], and [D] were used. The components used in each of the examples and comparative examples are as shown in Tables 1 to 3.

[0066] Component [A]: Reinforced fiber T800: Carbon fiber ("TORAYCA (registered trademark)" T800S-24K, manufactured by Toray Industries, Inc., strand tensile strength: 5.9 GPa) T1100: Carbon fiber ("TORAYCA (registered trademark)" T1100G-24K, manufactured by Toray Industries, Inc., strand tensile strength: 7.0 GPa) · T700: Carbon fiber ("TORAYCA (registered trademark)" T700S-24K, manufactured by Toray Industries, Inc., strand tensile strength: 4.9 GPa).

[0067] Component [C]: Thermoplastic resin PA6: Polyamide 6 ("Amilan" (registered trademark) CM1007 (manufactured by Toray Industries, Inc., melting point 225°C, glass transition temperature 48°C)) with a basis weight of 120 g / m 2 Film PPS: Polyphenylene sulfide ("TORELINA" (registered trademark) A670T05 (manufactured by Toray Industries, Inc., melting point 278°C, glass transition temperature 90°C)) with a basis weight of 120 g / m 2 Film PEKK1: Polyetherketoneketone ("KEPSTAN" (registered trademark) 6002 (manufactured by Arkema, melting point 300°C, glass transition temperature 160°C)) with a basis weight of 120 g / m 2 Film PEKK2: Polyetherketoneketone ("KEPSTAN" (registered trademark) 7002 (manufactured by Arkema, melting point 331°C, glass transition temperature 162°C)) with a basis weight of 120 g / m 2 Film PEEK: Polyetheretherketone (PEEK 450G (Victrex, melting point 343°C, glass transition temperature 143°C)) with a basis weight of 120g / m 2 Film PEI: Polyetherimide (ULTEM® 1010, manufactured by SABIC, glass transition temperature 217°C) with a basis weight of 120 g / m 2 Film Semi-aromatic PA: Polyamide 6T (melting point 320°C, glass transition temperature 125°C) with a basis weight of 120g / m 2 of film.

[0068] <Evaluation method for thermoplastic resin> (1) Method for measuring melting point and glass transition temperature of thermoplastic resin The melting points and glass transition temperatures of thermoplastic resins were measured using a differential scanning calorimeter (DSC) in accordance with JIS K7121 (2012). When multiple melting points or glass transition temperatures were observed for a mixture, the highest melting point was used as the melting point of the thermoplastic resin.

[0069] <Method of producing and evaluating thermosetting resin composition> The thermosetting resin compositions of the specific examples shown in Table 1 were prepared using the following compounds.

[0070] (1) Component [B]: Thermosetting resin (epoxy resin) Tetraglycidyldiaminodiphenylmethane ("Araldite" (registered trademark) MY721, Huntsman Advanced Materials, epoxy equivalent: 113 (g / eq.), tetrafunctional glycidylamine type epoxy resin) Bisphenol A epoxy resin ("jER" (registered trademark) 825, manufactured by Mitsubishi Chemical Corporation) Epoxy equivalent: 175 (g / eq.)) Phenol novolac epoxy resin ("jER" (registered trademark) 154, manufactured by Mitsubishi Chemical Corporation) Epoxy equivalent: 178 (g / eq.)) Bisphenol A type epoxy resin ("jER" (registered trademark) 1001, manufactured by Mitsubishi Chemical Corporation) epoxy equivalent: 475 (g / eq.).

[0071] (2) Amine compounds 4,4'-Diaminodiphenyl sulfone (Seikacure S, manufactured by Wakayama Seika Kogyo Co., Ltd.) Dicyandiamide (DICY7, manufactured by Mitsubishi Chemical Corporation).

[0072] (3) Curing catalyst 3-(3,4-Dichlorophenyl)1,1-dimethylurea (DCMU99, manufactured by Hodogaya Chemical Industry Co., Ltd.).

[0073] (4) Viscosity modifier Polyethersulfone ("Sumikaexcel" (registered trademark) PES5003P, manufactured by Sumitomo Chemical Co., Ltd.).

[0074] (5) Phosphorus compounds Red phosphorus flame retardant ("Nova Red" (registered trademark) 120, manufactured by Rinkagaku Kogyo Co., Ltd., phosphorus atom content 85% by mass).

[0075] (6) Method for preparing thermosetting resin composition The epoxy resin and viscosity modifier shown in Table 1 were placed in a kneading device, and heated and kneaded to dissolve the viscosity modifier (however, there are cases where the viscosity modifier is not added). Next, while continuing the kneading, the temperature was lowered to 100°C or lower, and an amine compound, a curing catalyst, and a phosphorus compound appropriately selected from those shown in Table 1 (the curing catalyst and phosphorus compound may not be added) were added and stirred to obtain thermosetting resin compositions B-1 to B-10.

[0076] <Method of producing and evaluating cured thermosetting resin> The thermosetting resin composition prepared by the above method was poured into a mold, heated in a hot air dryer from 30°C at a rate of 1.5°C / min to the curing temperature listed in Table 1, and then heated and cured for the curing time listed in Table 1, and then cooled to 30°C at a rate of 2.5°C / min to prepare a plate-shaped thermosetting resin cured product having a thickness of 2 mm. Component [B] is a cured product of the curable resin, and component [D] is a cured product of the thermosetting resin. The obtained cured thermosetting resin was evaluated for each of the specific examples listed in Table 1 by the following method.

[0077] <Method for measuring glass transition temperature and rubber-state elastic modulus of cured thermosetting resin> A test piece with a width of 12.7 mm and a length of 45 mm was cut out from the resin cured product plate prepared by the above method, and the test piece was dried in a vacuum oven at 60°C for 24 hours. A storage modulus curve was obtained by a dynamic viscoelasticity test according to JIS K 7244-7 (2007). The temperature value at the intersection of the tangent line in the glassy state and the tangent line in the transition state in the storage modulus curve was taken as the glass transition temperature. Here, the measurement was performed at a heating rate of 5°C / min and a frequency of 1 Hz. The storage modulus at a temperature 50°C higher than the obtained glass transition temperature was taken as the rubbery state modulus.

[0078] <Method for measuring bending strength of cured thermosetting resin> Test pieces 60 mm long and 10 mm wide were cut out from the cured resin plates prepared by the above method, and the test pieces were dried in a vacuum oven at 60°C for 24 hours. A three-point bending test was then carried out using a universal testing machine (Instron Japan Co., Ltd., "Instron" (registered trademark) 5565 model P8564) at a test speed of 2.5 mm / min and a support distance of 32 mm to determine the bending strength in accordance with JIS K7171 (1994).

[0079] <How to make prepreg> The prepregs were produced by the following two methods. The components used in each example are shown in Tables 2 and 3.

[0080] Prepreg [I] Reinforced fiber of component [A] (weight 193 g / m 2 ) is pulled out from the continuous reinforcing fiber sheet aligned in one direction, and while running in one direction, a reinforcing fiber sheet having a basis weight of 120 g / m2 composed of the component [C] is 2 The resin sheet was placed on the continuous reinforcing fiber sheet, heated with an IR heater to melt the component [C], and adhered to the entire surface of one side of the continuous reinforcing fiber sheet. Pressurized with a nip roll whose surface temperature was kept below the melting point of the component [C], the impregnated reinforcing fiber sheet was cooled to obtain a fiber-reinforced resin intermediate. The thermosetting resin composition related to the component [B] selected as shown in Tables 2 and 3 was applied to a resin area weight of 100 g / m using a knife coater. 2A release paper was coated with the composition to prepare a thermosetting resin film, and the thermosetting resin film was then placed on the surface of the intermediate opposite to the surface impregnated with the component [C]. The intermediate was impregnated with the thermosetting resin composition while being heated and pressurized with a heat roll, thereby obtaining a prepreg [I].

[0081] Prepreg [II] The thermosetting resin composition related to the component [B] selected as shown in Tables 2 and 3 was applied to a coating machine with a resin basis weight of 50 g / m 2 The resin film was coated on a release paper with the reinforcing fiber of the component [A] aligned in one direction (weight per unit area: 193 g / m 2 The carbon fibers were impregnated with the thermosetting resin composition while being heated and pressurized using heat rolls, to obtain prepreg [II].

[0082] <Laminate manufacturing method and mechanical property evaluation> (1) Measurement method for tensile shear bond strength The prepregs [I] and [II] prepared above were cut to a predetermined size to obtain two prepregs [I] and six prepregs [II]. The axial direction of the reinforcing fibers was defined as 0°, and the direction perpendicular to the axis was defined as 90°, so [0° / 90°] 2s (The symbol s indicates mirror symmetry) was laminated to prepare a preform. At this time, the two outermost layers on each side of the preform were laminated to be prepregs [I]. That is, the two prepregs [I] were laminated to sandwich six prepregs [II]. The preform was arranged so that both surface layers were thermoplastic resin layers containing the component [C]. That is, the surface of the prepreg [I] impregnated with the component [C] was arranged to be on the outside. This preform was set in a press molding die, and a pressure of 0.6 MPa was applied with a press machine while maintaining this shape using a jig or spacer as necessary, and a laminate was obtained by heating under the conditions described in Tables 2 and 3. The component [C] was present on the surface of the laminate.

[0083] The obtained laminate was cut into two pieces with a width of 250 mm and a length of 92.5 mm, with the 0° direction as the length direction of the test piece, and dried in a vacuum oven for 24 hours. Thereafter, the two panels cut into a width of 250 mm and a length of 92.5 mm were overlapped with a width of 25 mm and a length of 12.5 mm, with the 0° direction as the length direction, and a pressure of 3 MPa was applied at a temperature 20° C. higher than the melting point of the thermoplastic resin of the component [C] used, and held for 1 minute to weld the overlapped surfaces to obtain an integrated molded product. A tab was attached to the obtained integrated molded product in accordance with ISO4587:1995 (JIS K6850 (1994)), and the product was cut to a width of 25 mm to obtain the target test piece.

[0084] The obtained test pieces were dried in a vacuum oven for 24 hours, and the tensile shear bond strength was measured at environmental temperatures of 23°C and 80°C in accordance with ISO4587:1995 (JIS K6850(1994)). The results were evaluated as follows. The results are shown in the table. (a) Tensile shear bond strength at 23°C 28MPa or more: A 25MPa or more and less than 28MPa: B 20MPa or more but less than 25MPa: C Less than 20MPa: D (fail) (b) Tensile shear bond strength at 80°C 16MPa or more: A 13MPa or more and less than 16MPa: B 10MPa or more but less than 13MPa: C Less than 10MPa: D (fail).

[0085] (2) Method for measuring compressive strength The prepregs [I] and [II] prepared above were cut to a predetermined size to obtain two prepregs [I] and four prepregs [II]. The two outermost layers on each side were prepregs [I], and four prepregs [II] were sandwiched between them, and a total of six prepregs were laminated so that all had the same reinforcing fiber direction to produce a preform. At this time, both surface layers of the preform were arranged to be thermoplastic resin layers containing the component [C]. This preform was set in a press molding die, and if necessary, a jig or spacer was used to maintain this shape, and a pressure of 0.6 MPa was applied with a press machine, and the laminate was obtained by heating under the conditions described in Tables 2 and 3. The component [C] was present on the surface of the laminate.

[0086] After a tab was attached to the obtained laminate in accordance with SACMA-SRM 1R-94, a rectangular test piece 80 mm long and 15 mm wide was cut out with the reinforcing fiber axial direction as the length direction of the test piece. The obtained test piece was dried in a vacuum oven at 60 ° C for 24 hours, and the compressive strength was measured in an environment of 23 ° C using a universal material testing machine (Instron Japan Co., Ltd., "Instron" (registered trademark) 5565 type P8564) in accordance with SACMA-SRM 1R-94, and the test piece was evaluated based on the measurement results as follows. The results are shown in the table. 1.6GPa or higher: A 1.4GPa or more but less than 1.6GPa: B 1.2GPa or more but less than 1.4GPa: C Less than 1.2 GPa: D (Fail).

[0087] (3) Interlaminar fracture toughness (G IC and G IIC ) Measurement method The prepreg [I] prepared above was cut to a predetermined size, and all prepregs were laminated with the surface with the component [C] facing upward so that the reinforcing fiber direction was the same, for a total of 20 sheets. At this time, a release film for preliminary crack introduction was sandwiched between the 10th and 11th sheets in the center to prepare a preform. This preform was set in a press molding die, and, if necessary, a jig or spacer was used to maintain this shape, and a pressure of 0.6 MPa was applied with a press machine, and the laminate was obtained by heating at 180 ° C for 120 minutes. The component [C] was present between the layers of the laminate and on one surface.

[0088] From the obtained laminate, rectangular test pieces of 150 mm in length and 20 mm in width were cut out with the reinforcing fiber axis in the longitudinal direction of the test pieces, and were dried in a vacuum oven at 60°C for 24 hours. The obtained test pieces were subjected to the interlaminar fracture toughness (G IC and G IIC ) was evaluated.

[0089] <Measurement of the mean roughness length RSm and mean roughness height Rc in prepregs or laminates> The prepreg [I] or laminate prepared above is used. As shown in FIG. 1, in the case of the prepreg, an image of 1000 times magnification was taken using an optical microscope at an observation cross section 5 cut perpendicular to the prepreg plane direction at an angle of 45 degrees from a viewpoint perpendicular to the prepreg plane direction with respect to the fiber direction 4 of any [A] contained in both resin regions in a plan view of the prepreg, that is, at a viewpoint perpendicular to the prepreg plane direction. In an arbitrary observation range of 500 μm square in the obtained image, the roughness average length RSm and roughness average height Rc defined in JIS B0601 (2001) of the cross-sectional curve element obtained by the cross-sectional curve element measurement method 1 were measured. The same applies to the laminate.

[0090] <Examples 1 to 16> In Examples 1 to 16, laminates were produced by the method described in (1) Measuring method for tensile shear bond strength and (2) Measuring method for compressive strength.

[0091] <Examples 1 to 3> As shown in Table 1, in Examples 1 to 3, the rubber-state elastic modulus of the cured thermosetting resin tended to improve as the amount of trifunctional or higher glycidylamine epoxy resin (tetraglycidyldiaminodiphenylmethane) was increased. As shown in Table 2, the tensile shear bond strength and compressive strength improved as the amount of tetraglycidyldiaminodiphenylmethane was increased, showing a favorable trend.

[0092] <Example 1 and Comparative Examples 1 and 2> In Example 1, as shown in Table 2, by using a thermosetting resin having a high rubber-state elastic modulus as component [B], the laminate had superior tensile shear bond strength and compressive strength compared to Comparative Examples 1 and 2 shown in Table 3 (the thermosetting resin had a rubber-state elastic modulus of less than 10 MPa).

[0093] <Example 1, 4, and 5> As shown in Table 1, in Examples 4 and 5, a thermosetting resin composition different from that in Example 1 was used. As shown in Table 2, compared to Example 1, the tensile shear bond strength and compressive strength at 80°C tended to decrease slightly, but all of them exhibited excellent properties.

[0094] <Example 1, 6 and 7> As shown in Table 1, in Examples 6 and 7, compared to Example 1, there was a tendency for the bending strength of the cured thermosetting resin to decrease with an increase in the amount of phosphorus compound. As shown in Table 2, there was a tendency for the tensile shear bond strength at 23°C and the tensile shear bond strength at 80°C to decrease slightly. However, all of the examples showed excellent properties.

[0095] <Example 1 and Example 8> As shown in Table 2, Example 8 was prepared in the same manner as Example 1, except that no viscosity modifier was used. As shown in Table 2, Example 8 showed excellent properties similar to those of Example 1.

[0096] <Example 1 and Examples 9 and 10> As shown in Table 2, in Examples 9 and 10, reinforcing fibers with different strand tensile strengths were used. Compared to Example 1, the higher the strand tensile strength, the more improved the tensile shear bond strength at 23°C and the tensile shear bond strength at 80°C were, demonstrating favorable properties.

[0097] <Example 1 and Examples 11 to 16> As shown in Table 2, in Examples 11 to 16, when a component [C] having a higher glass transition temperature than that of Example 1 was used, the tensile shear bonding strength at 80°C was improved compared to Example 1, and preferable characteristics were exhibited.

[0098] <Example 1 and Comparative Example 3> A film with a basis weight of 50g / m is applied to both sides of a reinforced fiber sheet arranged in a unidirectional plane. 2 A film of polyamide 6 ("Amilan" (registered trademark) CM1007 (manufactured by Toray Industries, Inc.)) was attached to the sheet, and the sheet was heated and pressed at 250°C to give a reinforced carbon fiber basis weight of 193 g / m. 2 The prepregs obtained were cut to a predetermined size and then split into [0° / 90°] pieces for evaluation of bonding strength and compression strength. 2s Alternatively, six sheets were laminated in the same direction, and then a pressure of 3 MPa was applied using a press machine, and the laminate was heated at 250°C for 10 minutes to obtain a laminate. The bonding strength and compressive strength of the obtained laminate were measured using the method described in the Examples. As shown in Table 3, since the laminate did not contain a thermosetting resin, the tensile shear bonding strength and compressive strength at 80°C were lower than those of Example 1, and the laminate did not exhibit sufficient properties as a structural material.

[0099] <Example 17 and Comparative Examples 4 and 5> In Example 17, (3) interlaminar fracture toughness value (G IC and G IIC) to prepare a laminate. The prepreg [I] was cut to a predetermined size, and 20 sheets of all prepregs were laminated with the surface with the component [C] facing upward so that the reinforcing fiber direction was the same, and a release film for preliminary crack introduction was sandwiched between the 10th and 11th sheets in the center to prepare a preform. In Comparative Example 4, prepreg [II] (not containing component [C]) was cut to a predetermined size, laminated in the same manner as in Example 17, and a release film was sandwiched to obtain a preform. In Comparative Example 5, polyamide particles (SP-500, manufactured by Toray Industries, Inc.) were applied to one surface of prepreg [II] (not containing component [C]) cut to a predetermined size, and the amount of particles per unit area of ​​the prepreg was 7 g / m. 2 After uniformly dispersing the mixture, the mixture was laminated in the same manner as in Example 17, and a release film was sandwiched between the layers to obtain a preform. In both Example 17 and Comparative Examples 4 and 5, the obtained preform was subjected to a pressure of 0.6 MPa in a press and heated at 180°C for 120 minutes to obtain a laminate, and the interlaminar fracture toughness (G IC and G IIC ) was evaluated. As shown in Tables 2 and 3, Example 17, which contains the component [C] between the layers of the laminate, exhibited a superior interlaminar fracture toughness value compared to Comparative Example 4, which does not contain the component [C], and Comparative Example 5, which contains a thermoplastic resin in a different form.

[0100] [Table 1]

[0101] [Table 2-1]

[0102] [Table 2-2]

[0103] [Table 3] [Explanation of symbols]

[0104] 1: A layer constituting a prepreg or laminate 2: Component [A] 3: Component [C] and Component [B] or Component [C] and Component [D] 4: Fiber direction 5: Observation cross section 6: Component [A] 7: Resin region containing component [C] 8: Resin region containing component [B] or resin region containing component [D] 9: Observation image 10: Boundary 11: Reference line 12: Orthobase line 13: Cross section curve

Claims

1. A prepreg comprising the following components [A], [B] and [C]: [B] has a rubber-state elastic modulus of 10 MPa or more at a temperature 50° C. higher than the glass transition temperature when the degree of cure is 90% or more; [C] is present on the surface of the prepreg, A prepreg in which the reinforcing fibers [A] contained in a resin region containing [B] and a resin region containing [C] are present across the boundary surface between both resin regions, the resin region containing [B] and the resin region containing [C] are adjacent to each other in layers to form the boundary surface, the reinforcing fibers are in the form of continuous fibers, and the reinforcing fiber mass content is 30 to 90 mass%. [A] Reinforced fiber [B] Thermosetting resin [C] Thermoplastic resin

2. 2. The prepreg according to claim 1, wherein, in a plan view of the prepreg, when a cross section perpendicular to a prepreg plane including the [A] is obtained from a direction at an angle of 45 degrees different from the fiber direction of any [A] contained in both resin regions, the cross section formed by the boundary surface where the two resin regions are in close contact has a roughness average length RSm defined in JIS B0601 (2001) of 100 μm or less and a roughness average height Rc of 3.5 μm or more.

3. 3. The prepreg according to claim 1 or 2, wherein component [B] has a rubber-state elastic modulus of 12 MPa or more at a temperature obtained by adding 50° C. to the glass transition temperature at a degree of cure of 90% or more.

4. 3. The prepreg according to claim 1 or 2, wherein component [B] has a rubber-state elastic modulus of 15 MPa or more at a temperature obtained by adding 50° C. to the glass transition temperature at a degree of cure of 90% or more.

5. Component [B] contains an epoxy resin, 5. The prepreg according to claim 1, wherein the component [B] contains 40 to 100 parts by mass of a tri- or higher functional glycidyl amine type epoxy resin relative to 100 parts by mass of all epoxy resins contained in the component [B].

6. The prepreg according to any one of claims 1 to 5, wherein the composition containing component [B] contains an aromatic amine.

7. The prepreg according to any one of claims 1 to 6, wherein the composition containing component [B] contains phosphorus in an atomic concentration of 1.0 mass% or less.

8. 8. The prepreg according to any one of claims 1 to 7, wherein the component [B] has a flexural strength of 150 MPa or more when the degree of cure is 90% or more.

9. The prepreg according to claim 2, wherein the roughness average height Rc is 10 μm or more.

10. 10. The prepreg according to any one of claims 1 to 9, wherein the component [C] is one or more types selected from a crystalline thermoplastic resin having a glass transition temperature of 80°C or higher and an amorphous thermoplastic resin having a glass transition temperature of 160°C or higher.

11. The prepreg according to any one of claims 1 to 10, wherein the component [C] is one or more selected from polyarylene ether ketone, polyphenylene sulfide, or polyetherimide.

12. 12. The prepreg according to any one of claims 1 to 11, wherein component [A] contains carbon fibers having a strand tensile strength of 5.5 GPa or more.

Citation Information

Patent Citations

  • Prepreg and fiber-reinforced composite material

    JP1996259713A

  • Carbon fiber reinforced resin molded product and its manufacture

    JP1998138354A

  • Epoxy resin composition, prepreg, and fiber-reinforced composite material

    JP2017088652A

  • Adhesion structural member

    JP2018161801A

  • Prepreg and fiber-reinforced composite material

    JP2019038939A